2018
DOI: 10.14740/wjon1093w
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Provider Volume on Outcomes of Patients With Hodgkin Lymphoma

Abstract: BackgroundWhile the provider volume-outcome relationship has been established for many complex surgeries and invasive procedures, the provider volume impact on outcomes for Hodgkin lymphoma (HL) is less certain. We hypothesized that high-volume providers (HVPs) may have superior outcomes compared with low-volume providers (LVPs).MethodsWe performed a chart-based, retrospective review of all patients receiving adriamycin, doxorubicin, bleomycin, vinblastine, and dacarbazine (ABVD) for HL at the West Cancer Cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…The association of better survival with increased clinical volume has been identified in hematologic oncology within populations and single institutions. 10,[12][13][14] However, this has not been addressed for nonhematologic cancers at the provider level. The Ontario jurisdiction offered a unique opportunity to study this question, with data on all therapies, consultations, and outcomes reliably available for an entire population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association of better survival with increased clinical volume has been identified in hematologic oncology within populations and single institutions. 10,[12][13][14] However, this has not been addressed for nonhematologic cancers at the provider level. The Ontario jurisdiction offered a unique opportunity to study this question, with data on all therapies, consultations, and outcomes reliably available for an entire population.…”
Section: Discussionmentioning
confidence: 99%
“…Increased clinical volume has been associated with higher quality of care and better outcomes in hematologic cancers. [10][11][12][13][14] However, whether medical oncologists' clinical experience and volume affect patterns of care and outcomes of systemic therapy in solid cancers is unknown. In a review of volume outcome in cancer care, the Institute of Medicine outlined the need to examine volume-outcome relationships in both surgical and medical interventions.…”
Section: Introductionmentioning
confidence: 99%
“…In one singlecenter study, it was found that patients treated by oncologists who treated more than 3 patients with Hodgkin lymphoma (with inpatient chemotherapies) had better survival outcomes than those treated by physicians who handled fewer than 3 Hodgkin lymphoma-related inpatient chemotherapies. 18 The authors found that low-volume providers (providers treating fewer than 3 patients with Hodgkin lymphoma annually) were more likely to hold chemotherapy doses for afebrile neutropenia. 18 Moreover, low-volume providers were more likely to prescribe dose delays than their counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…18 The authors found that low-volume providers (providers treating fewer than 3 patients with Hodgkin lymphoma annually) were more likely to hold chemotherapy doses for afebrile neutropenia. 18 Moreover, low-volume providers were more likely to prescribe dose delays than their counterparts. 18 High-volume centers may have more experienced multidisciplinary care geared toward lymphoma management, especially radiologists who evaluate the interim positron emission tomography response by the Deauville system, which may affect management decisions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation